2004
DOI: 10.1074/jbc.m401781200
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Domain and Motif Analyses of Androgen Receptor Coregulator ARA70 and Its Differential Expression in Prostate Cancer

Abstract: Androgen receptor (AR)-associated coregulator 70 (ARA70) was the first identified AR coregulator. However, its molecular mechanism and biological relevance to prostate cancer remain unclear. Here we show that ARA70 interacts with and promotes AR activity via the consensus FXXLF motif within the ARA70-N2 domain (amino acids 176 -401). However, it does not promote AR activity via the classic LXXLL motif located at amino acids 92-96, although this classic LXXLL motif is important for ARA70 to interact with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 60 publications
3
69
1
Order By: Relevance
“…The positive signal was blocked by antigenic peptide, and preimmune serum showed no immunoreactivity above background. These data correlate well with previous reports demonstrating that whereas ARA70␣ expression is decreased, 8,21 total ARA70 (␣ and ␤) is increased in prostate cancer, 17 suggesting ARA70␤ expression is increased in cancer.…”
Section: Increased Expression Of Ara70␤ In Human Prostate Cancersupporting
confidence: 92%
See 1 more Smart Citation
“…The positive signal was blocked by antigenic peptide, and preimmune serum showed no immunoreactivity above background. These data correlate well with previous reports demonstrating that whereas ARA70␣ expression is decreased, 8,21 total ARA70 (␣ and ␤) is increased in prostate cancer, 17 suggesting ARA70␤ expression is increased in cancer.…”
Section: Increased Expression Of Ara70␤ In Human Prostate Cancersupporting
confidence: 92%
“…A previous report also shows cytoplasmic localization of ARA70␤, although the antibody used in that experiment recognizes both ␣ and ␤ forms. 17 The localization of ARA70␤ in the cytoplasm may suggest an indirect or class II AR co-activator function, whereas ARA70␣ likely functions as classic nuclear or class I co-activator. 17 Together with its increased expression in prostate cancer, ARA70␤ stimulates prostate cancer growth in an androgen-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that the increase in coactivator expression leads to an increase in AR-regulated gene expression, for instance, ARA70 increases AR expression, stability, and nuclear translocation. 52 Thus, overexpression and recruitment of coactivator proteins to the AR-binding sites may facilitate the progression of HR PCAs.…”
Section: Amplification Of the Armentioning
confidence: 99%
“…Both SRC-1 and ARA70 are expressed in human prostate cancer cell lines and in normal prostate, in the luminal epithelial cells that also express AR (Gregory et al, 2001;Linja et al, 2001;Hu et al, 2004;Powell et al, 2004;Agoulnik et al, 2005). There is both in vitro and in vivo evidence that SRC-1 is required for optimal androgen signalling and growth in the prostate, since knockdown of SRC-1 attenuated growth and androgendependent gene expression in androgen-sensitive prostate cancer cell lines (Agoulnik et al, 2005), and SRC-1-null mice exhibit attenuation of androgenstimulated prostatic growth (Xu et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…At the mRNA level, however, decreased or unaltered SRC-1 levels in malignant versus benign prostate have been reported (Fujimoto et al, 2001;Linja et al, 2004;Maki et al, 2006). Studies on expression of ARA70 in prostate cancer are equally contradictory with the co-activator being found to be both upregulated at the protein level (Hu et al, 2004) and downregulated at the RNA level (Li et al, 2002) in tumours versus benign tissue, whereas others have found no change in mRNA levels (Mestayer et al, 2003). In light of the current study, a possible explanation of the conflicting results of such studies could be differences in hormonal treatment regimes in the patients.…”
Section: Discussionmentioning
confidence: 99%